The added value of anosmic subtype on motor subtype in Parkinson’s disease: a pilot study - Chia-Yen Lin; Hsiao-Hui Chen; Ching-Heng Lin; Ming-Hong Chang (Scientific Reports)
Abstract This study investigates whether incorporating olfactory dysfunction into motor subtypes of Parkinson’s disease (PD) improves associations with clinical outcomes. PD is commonly divided into motor subtypes, such as postural instability and gait disturbance (PIGD) and tremor-dominant PD (TDPD), but non-motor symptoms like olfactory dysfunction remain underexplored. We assessed 157 participants with PD using the University of Pennsylvania Smell Identification Test (UPSIT), Movement Disorder Society-Sponsored Revision of the Unified Parkinson’s Disease Rating Scale (M-UPDRS), Montreal Cognitive Assessment (MoCA), 39-item Parkinson’s Disease Questionnaire Summary Index (PDQ-39 SI), and 99mTc-TRODAT-1 imaging. Motor subtypes were categorized as PIGD and TDPD, and olfactory subtypes were categorized as total anosmia (TA) and non-anosmia (NA). Significant differences were observed, with the highest disease burden occurring in PIGD TA, while the lowest occurred in TDPD NA. The total M-UPDRS scores (59.0, 47.5, 43.0, 36.0; p < 0.001) and PDQ-39 SI scores (22.4, 22.8, 9.6, and 9.0; p < 0.001) varied significantly across groups, and the highest occurred for PIGD TA, followed by PIGD NA, TDPD TA, and TDPD NA. MoCA scores indicated the best cognitive performance in TDPD NA (p = 0.002). Thus, the results show that integrating olfactory dysfunction with motor subtypes may enhance PD classification, particularly in cognitive assessment in cases of TDPD.